The COVID-19 and the changes in Latin American and European integration (2021)
The covid-19 pandemic has led to a moment of reflection for the integration processes of Latin America, which have been overwhelmed by its impact and consequences in the absence of appropriate multilateral, collaborative and consensual responses, preferring to act individually with the prevalence of national sovereignties over a performance of shared sovereignties. This is showing that one of the greatest shortcomings and weaknesses of Latin American integration is found in the institutional sphere, to which is added the lack of leadership; so necessary in circumstances such as these. Latin America has not acted in a collaborative way, despite having so many elements of shared identity, which has reduced the possibility of making better use of international aid. This is evident, when compared with the advances in other continents or countries, like the observed multilateral reaction of the European Union and even greater coordination in the African, which allowed them to take better advantage of the cooperation actions proposed, for example, by China. Although at the beginning there was some delay in the direction of the European Union, finally a package of economic measures of great magnitude was approved that will allow many of its members to more effectively avoid the negative impacts of the pandemic. In terms of leadership, the Franco-German axis and the behavior of a federal state like Germany is also a source of positive lessons. In Latin America, only the Central American integration process has seen more collaborative action, while in processes such as Mercosur it is clear that there is a need to introduce profound reforms that clarify the course of the process and incorporate essential elements into this and other integration processes for the post-pandemic as joint, multilateral and solidarity efforts.